Jual Beli Dengan Sistem Dropshipping Dalam Kajian Hadist - Muhammad Aziz Zakiruddin (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2021)
Background. Dropshipping is a tangible form of the development of buying and selling mechanisms that follow technological developments. The Dropshipping mechanism makes it easy for people who want to start entrepreneurship, even without capital, the mechanism is simple, only as a third party who acts as a liaison, as well as a mechanism that does not require the seller to stock up on goods first like the Reseller mechanism, encouraging public interest to use the mechanism. even well-known online buying and selling sites include this mechanism. Then how is this buying and selling mechanism in Islamic law?, with the hadith that prohibits buying and selling goods that do not exist. Aim. This article examines the Dropshipping mechanism in the perspective of Hadith. Methods. This research is a qualitative library research. Results. Hadith explicitly prohibits buying and selling of goods that are not owned, but it is different from buying and selling orders or greetings. The dropshipping buying and selling mechanism is actually a sale and purchase of greetings, but with a slightly different mechanism. This mechanism is actually not in the category of selling something that is not owned, but there must be a clear contract between the dropshipper and the supplier.